Climate Anxiety Among English-Speaking Youth in Québec - Pettem, Alexandre; Rengel, Fernanda (2023)

Swimming Upstream : Investigating the Barriers to Aquatic Equity for Québec’s English-speaking BIPOC Youth Communities - Porras-Gil, Javier Armando (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 25

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 10

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 15

A Public Transportation Renaissance in a Post-Pandemic Context - Gherman, Stefan (2023)

Mental Health in the Anthropocene : Climate Anxiety among Québec’s English-speaking Youth - Rengel, Fernanda; Pettem, Alexandre (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

Law 96: College Instruction in the Minority Language - Rengel, Fernanda (Youth for Youth Québec (Y4Y Québec), 2023)
Bill 96, An Act respecting French, the official and common language of Québec, was proposed to the National Assembly on May 13, 2021. It was sponsored by Coalition Avenir Québec MNA, M. Simon Jolin-Barrette, who at the time served as Minister Responsible for the French Language1 (Assemblée Nationale du Québec). The bill proposed several amendments overhauling the Charter of the French language, colloquially known as Bill 101, which had received royal assent in 1977. The stated purpose of Bill 96 was a renewed focus on strengthening the use of French–Québec’s sole official language– in all spheres of public life. Among other elements, the bill involves establishing francization frame- works in the workplace, as well as specifying Québec’s role in expanding and promoting francophone and Acadian communities, both within Canada and abroad (Bill 96 3). The bill received royal assent on June 1st, 2022, becoming Law 96. Being considered in this brief are Law 96’s amendments to the 1977 Charter of French with regard to college instruction in English. These impose certain expectations and limitations on college-level instruction in the minority language as the Charter did to primary and secondary instruction in the minority language in 1977.

Projet de loi 96 : Changements apportés à l’enseignement collégial dans la langue minoritaire - Rengel, Fernanda (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 23

Residential Precarity : Youth and Housing in Québec’s Urban Centres - Rodriguez, Chloe (Y4Y Québec, 2023)

Residential Precarity: Youth and Housing in Québec’s Urban Centres - Rodriguez, Chloe (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 18

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20